PERSENTASE HEART RATE REVERSE PENARI LEGONG KERATON LASEM PADA MAHASISWI PROGRAM STUDI SENI TARI INSTITUT SENI INDONESIA DENPASAR TAHUN 2014 - Pertiwi, Ni Luh Tu; Muliarta, I Made (E-Jurnal Medika Udayana; Vol 6 No 9 (2017): E-Jurnal Medika Udayana, 2017)
Bali with a strong culture still have a lot of people who love to dance traditional dances. One of the popular Balinese dance that is still often danced and taught to the Balinese people in early age is Legong Keraton Lasem. Activities dancing Legong Keraton Lasem Dance can be used as an attempt to increase the level of physical activity in addition to the modern sports world today recognized as basketball, tennis, and others. The purpose of this study was to determine the average resting heart rate, working pulse, work pulse, heart rate reverse percentage (% HRR) of Legong Keraton Lasem dancer on the Dance Studies Program’s student of Art Institute Indonesia Denpasar 2014. This study is cross-sectional descriptive study using consecutive sampling technique. Obtained 49 female sample that meet the inclusion criteria, with one subject dropped out. Result from this study was found that average resting heart rate, working pulse, and work pulse of samples was 77.74 pulse beats/minute, 129.37 beats/minute, and 51.89 beats/minute. Conclusion of this study was found percentage of heart rate reverse (%HRR) of Legong Keraton Lasem Dancer on The Dance Studies Program’s students of Art Institute Indonesia Denpasar 2014 was equal to 50.31%. It showed that dance a Legong Keraton Lasem in 20 minutes for 3-5 times a week, Legong Keraton Lasem could be categorized as a exercise for physical fitness. Keywords : heart rate reverse, Legong Keraton Lasem Dance, Denpasar